Total Quality Management as the Key of the Company to Gain the Competitiveness, Performance Achievement and Consumer Satisfaction - Ramlawati, Ramlawati; Putra, Aditya Halim Perdana Kusuma (International Review of Management and Marketing, 2018)
A decreasing number of manufacturing industries in some sectors in the region of Makassar city from the year 2012 to 2016 is generally influenced by the economic climate and is also affected by the poor performance and inability to compete and lack of attention to some industry on the application of TQM in their companies. TQM is an important concern because it involves all elements of management and continuously improving in order to shape the company's well performance and to create the consumers' satisfaction so that the business continuity can be maintained. This study took a sample of 43 large-scale manufacturing companies with the number of respondents consists of 129 managers, with the data collection using questionnaires. The research approach uses explanatory research by making the SEM (Structural Equation Model) as a tool of analysis test. The results of this study stated that the better implementation of TQM practices the more increase in the competitiveness of the company, consumers' satisfaction, and business performance, the better competitiveness is also increasing the consumers' satisfaction but does not affect the business performance of these manufacturing companies in Makassar. Keywords: Total Quality Management, Consumer Satisfaction, Competitiveness JEL Classifications: L6, M0, M2 https://doi.org/10.32479/irmm.6932